2019
DOI: 10.1097/tp.0000000000002645
|View full text |Cite
|
Sign up to set email alerts
|

Deceased Donor–initiated Chains: First Report of a Successful Deliberate Case and Its Ethical Implications

Abstract: Background: The utilization of deceased donor kidneys to initiate chains of living donor kidney paired donation (KPD) has been proposed, although the potential gain of this practice needs to be quantified and the ethical implications must be addressed before starting its application. Methods: The gain of implementing deceased donor-initiated chains has been measured through a mathematical algorithm, using retrospective data on the pool of donor/recipient incompatible pairs at a single Center. Allocation rules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
(11 reference statements)
0
15
0
2
Order By: Relevance
“…In this article, we considered the simplest of possible chains created by the DD‐CIK, where the donation to a candidate in the KPDP is followed by a donation by that candidate's LD to the DD waitlist. There would be possibilities of longer chains, 20‐22 and we are investigating these, but this simplest case is of interest in its own right because each transaction involving a DD‐CIK is typically concluded in a few days. In addition, we have demonstrated that this approach results in a substantial increase in the number of transplants achieved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this article, we considered the simplest of possible chains created by the DD‐CIK, where the donation to a candidate in the KPDP is followed by a donation by that candidate's LD to the DD waitlist. There would be possibilities of longer chains, 20‐22 and we are investigating these, but this simplest case is of interest in its own right because each transaction involving a DD‐CIK is typically concluded in a few days. In addition, we have demonstrated that this approach results in a substantial increase in the number of transplants achieved.…”
Section: Discussionmentioning
confidence: 99%
“…There would be possibilities of longer chains, [20][21][22] and we are investigating these, but this simplest case is of interest in its own right because each transaction involving a DD-CIK is typically concluded in a few days. In addition, we have demonstrated that this approach results in a substantial increase in the number of transplants achieved.…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations